The moral conduct. Ethical dilemmas, the role of the deontological code in social work - Nina Stănescu, (Technium Social Sciences Journal, 2020)
The most acute symptom of modernity is the ethical component of society, the so-called spiritual crisis. The essence of moral crisis consists in reducing religiosity; the major effects of diminishing religiosity are: blind obsession for money, selfishness, proliferation of the lack of honesty, decline of the family as a social institution, public proliferation of sexuality, increase of discord, amplification of conflicts of all kinds (between individuals, between the individual and society, between social groups, between generations). The real world alienated itself and even broke away entirely from the world of spiritual, social and moral life. Nowadays, we talk about science, politics, religion, culture, economics, as if they were different fields, as if the involvement of a problem from one field into another field would not be allowed. In this sense, culture should not be involved in matters of science, morality cannot be compatible with business; and in politics we cannot guide ourselves by moral principles. Such attitudes lead to antisocial and deviant patterns of behavior: lying, violence, discrimination, corruption, tax evasion, crime etc.